2017
DOI: 10.1002/slct.201701756
|View full text |Cite
|
Sign up to set email alerts
|

Poly(3,4-propylenedioxypyrrole) Nanofibers with Branched Alkyl Chains by Electropolymerization to Obtain Sticky Surfaces with High Contact Angles

Abstract: Inspired by natural species such as rose petals or Echeveria pulvinata leaves with both high water contact angle θw and high water adhesion (also called parahydrophobic), we have prepared poly(3,4‐propylenedioxypyrrole) with branched alkyl chains on the 3‐position by electropolymerization. The grafting at the 3‐position keeps the NH group free, which is an important condition to obtain nanofibers. Different lengths of branched alkyl chains are studied. Here, using extremely long branched alkyl chains (ProDOP‐b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 46 publications
1
6
0
Order By: Relevance
“…The monomer oxidation potentials were first determined by cyclic voltammetry and were found to be approximately 0.9 V (vs. SCE) for the EDOP derivatives and 1.1 V (vs. SCE) for the ProDOP derivatives. These oxidation potentials are consistent with previous results reported in the literature . In these experiments, the alkyl chain length did not significantly influence the monomer oxidation potential because they are distant from the polymerizable sites.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The monomer oxidation potentials were first determined by cyclic voltammetry and were found to be approximately 0.9 V (vs. SCE) for the EDOP derivatives and 1.1 V (vs. SCE) for the ProDOP derivatives. These oxidation potentials are consistent with previous results reported in the literature . In these experiments, the alkyl chain length did not significantly influence the monomer oxidation potential because they are distant from the polymerizable sites.…”
Section: Resultssupporting
confidence: 93%
“…Among the many possibilities, members of the 3,4‐alkylenedioxypyrrole (XDOP) family, such as 3,4‐ethylenedioxypyrrole (EDOP) and 3,4‐propylenedioxypyrrole (ProDOP), are exceptional monomers for their ultra‐low potential and polymerize to give materials with unique opto‐electronic properties, including high conductivity, multicolor cathodic and anodic electrochromism, and rapid redox switching . In order to obtain nanofibers using XDOP with high hydrophobicity, it is preferable to position the substituent on the bridge (not on the nitrogen atom) in order to keep the NH group free and favor the formation of nanofibers by hydrogen bonding . Previously, a method was found to obtain EDOP and ProDOP derivatives with hydroxy groups on the bridge using epibromohydrin .…”
Section: Introductionmentioning
confidence: 99%
“…It should also be noticed that compared to previous works on PEDOP or ProDOP polymers substituted on the bridge, the results with linear or branched alkyl chains gave higher parahydrophobic properties because of the possible formation of long nanofibers structures, depending on their length. 19,30…”
Section: Results and Discussionmentioning
confidence: 99%
“…Following the used process, conducting polymers can form nanostructured materials. This is possible not only in solution by self-assembly but also directly on surfaces inducing a high influence of the surface properties. The electropolymerization was revealed as a very interesting process because of an easy and fast control of the surface structures using various electrochemical parameters. In this process, a monomer is oxidized to form conducting polymers onto conductive substrates that are used as a working electrode such as gold, platinum, titanium, stainless steel, or indium tin oxide, whatever the surface geometry is (flat substrates, textured substrates, meshes, fabrics...). In this process, the monomer also plays a key role not only in the polymerization but also in the control of the surface morphology and wettability.…”
Section: Introductionmentioning
confidence: 99%
“…For the formation of nanofibers, it is preferable to keep amino (NH) groups free, favoring hydrogen bonds. Indeed, it is possible to place the substituent on the 3,4-ethylenedioxy bridge. , Fortunately, it was reported that a very interesting way to synthesize both EDOP and ProDOP derivatives with hydroxyl groups on the bridge is through the reaction with epibromohydrin . The formation of nanofibers was found to be possible using fluorinated chains.…”
Section: Introductionmentioning
confidence: 99%